Information manpower capacity building for decentralization in Uganda through industrial training - Magara, Elisam; Nyumba, Joyce Bukirwa (IFLA journal, 2002)
Information is a key resource for development. Information can be kept in registries, records centres, archives, libraries, resource centres, research centres, documentation centres and in public offices. Information is contained in different types of media including paper (records, documents, text), audiovisual, computer based, etc. A lot of infonnation is being generated every other day in public offices in Uganda and it is likely to increase with continued empowerment of the population. There is a need for manpower to organize and process information for timely and opti- mum utilization. The Constitution of the Republic of Uganda’ provides a National Objective of National Sovereignty, Independence and Territorial Integrity which states that The State shall endeavour to mobilise, organise,